Replacement of the Aortic Arch - Altieri, Carlos; Mazza, Milton; Pagliari, Luis; Quiroz, Darío; ´Fronzzutti, Agustín; Lapiedra, Eduardo; Maldonado, Oscar (Cirugía del Uruguay, 1980)
The authors present one case of a siphilitic thoracic aneurysm, of ascendent aorta and arch, operated under deep hypothermia and total circulatory stop, using a simple replacement technic having done only two anastomosis.